Improving the Psychological Well-Being of Post-Pandemic Students through Optimistic Thinking Training - Dewi Kamaratih; Gilang Mukti Rukmana; Alfiza Fakhriya Haq (Indonesian Journal of Cultural and Community Development, 2023)
One of the changes that have occurred in the field of education after the COVID-19 pandemic is the drastic change in the learning model, where teaching and learning activities are carried out online. This requires students to adapt quickly. This adjustment has an impact on students' psychological well-being as they deal with the changes that occur. The psychological well-being of post-pandemic students is in the low and medium categories, so an effort is needed to improve this condition. The optimistic thinking training aims to help students improve their psychological wellbeing after the pandemic. The stages in this program are providing optimistic thinking interventions using the ABCDE (Adversity, Belief, Consequences, Disposition, and Energization) method. The result of this training is an increase in psychological well-being among students who take part in the training program. Having psychological well-being can help students master and adapt to the environment effectively, establish positive relationships with others, and develop their potential from time to time. Highlights: Rapid Adaptation: Students faced a rapid shift to online learning during the pandemic, requiring quick adaptation to a new learning model. Optimistic Thinking Training: Implementing the ABCDE method, optimistic thinking training aims to improve the psychological well-being of post-pandemic students. Benefits of Psychological Well-Being: Improved psychological well-being helps students effectively navigate their environment, establish positive relationships, and maximize their potential. Keywords: online learning, psychological well-being, optimistic thinking training, post-pandemic students, adaptation.